PEMBERIAN URIN SAPI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Ilham M Ilham M; Hapsoh Hapsoh; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Sweet corn cultivation has several obstacles, namely reduced cultivated area, limited productive land area, high level of land conversion and low soil fertility. One of the efforts to increase soil fertility is the giving of cow urine and NPK fertilizer because it can improve the physical, biology and soil chemistryproperties. This study aims to determine the effect of cow urine and NPK fertilizer combination and get the best dose of growth and production of sweet corn (Zea mays saccharataSturt). This experiment was conducted experimentally using Factorial Randomized Block Design consisting of 2 factors and 3 replications, namely cow urine (0.75 ml/plant) and NPK factor (250, 350, and 450 kg/ha). The observed data obtained were analyzed using analysis of variance and continued with Duncan test at 5%. The results showed that giving of cow urine and NPK fertilizer had a significant effect in increasing the growth and production of sweet corn plant. Giving 75 ml of cow urine/plant and NPK fertilizer 450 kg/ha had the best ability to increase the growth and production of sweet corn.Key words: Sweet corn, cow urine, NPK fertilizer.